Spatiality, Maps, and Mathematics in Critical Human Geography: Toward a Repetition with Difference. Issue 1 (2nd January 2018) - O'Sullivan, David; Bergmann, Luke; Thatcher, Jim E.
Abstract : Quantitative and cartographic methods are today often associated with absolute, Newtonian conceptions of space. We argue that some such methods have not always been and need not be so allied. Present geographic approaches to relational space have been largely advanced through radical political economic and feminist thought. Yet we identify quantitative and cartographic methods (taking as exemplars a range of thinkers, some of whom were most prominent in the 1960s and 1970s) that can contribute to these approaches to relational space. We suggest neglected methods to revisit, new alliances to be forged with critical human geography and cultural critique, and possible paths to enliven geographical imaginations.